TRANSFER PASSIVE OF ANTIBODY BY USING THE IMMUNOGLOBULIN AS PROTEIN NUTRIENT IN COLOSTRUM IN RESPONSE TO THE MORTALITY RATE IN BUFFALOES (Review Article) - Rumokoy, Laurentius J.M. (Proceeding Buffalo International Conference, 2013)
Neonate losses are very important case in Bovidae animals in the country of Indonesia, which is due to the virus, bacteria or parasites in conjunction with failure of passive transfer (FTP). As the effect of this infection, the angiogenesis complication could be occurred. Consequently, it is very urgent to break down these problems by realizing a scientific strategy on immunoglobulin-G (IgG) passive transfer in neonates. The existence of neonates life naturally depends on environmental conditions included to the nutrients supplied by their mother. The proteins immunoglobulin contained in the motherâs colostrums are essential nutrients for immunity system of the newborn. This article aims to present the use of protein nutrient in colostrums through passive transfer of antibodies as a strategy in response to the high mortality rate in buffaloes in Indonesia, particularly in traditional buffalo maintenance system. In a farm system like this has a high risk of infection in the new born animal. Limitations on the immune system of a new born buffalo occurred because in the uterus, a variety of antibody molecules from mother circulation can not be transferred through the placenta to embryo. Consequently in the new ex-utero environment, such individuals are very susceptible to various infections of Â pathogenic microorganisms.